2007
DOI: 10.1530/eje-07-0150
|View full text |Cite
|
Sign up to set email alerts
|

Delayed pubertal onset and development in German children and adolescents with type 1 diabetes: cross-sectional analysis of recent data from the DPV diabetes documentation and quality management system

Abstract: Objective: To investigate the effect of type 1 diabetes on pubertal onset and development, and to identify factors potentially affecting puberty, including glycemic control, relative diabetes duration, body mass index standard delta score (BMI SDS), insulin dose, and intensity of insulin therapy. Research design and methods: Initiated in 1990, the Diabetes-Patienten-Verlaufsdaten (DPV) is an ongoing, prospective longitudinal follow-up program to benchmark the quality of diabetes care provided to, predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…In our study, we observed that T1D girls exhibit a delay in the attainment of breast Tanner stages 3 and 4 [2]. The German study documented a delay of 4 months for Tanner stage 3 only [1, 2], and pubic hair Tanner stages 3 and 4 were delayed in T1D girls from both studies.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 58%
See 4 more Smart Citations
“…In our study, we observed that T1D girls exhibit a delay in the attainment of breast Tanner stages 3 and 4 [2]. The German study documented a delay of 4 months for Tanner stage 3 only [1, 2], and pubic hair Tanner stages 3 and 4 were delayed in T1D girls from both studies.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 58%
“…The T1D subjects were treated with 1–7 daily injections and the control group was derived from a large cross-sectional study evaluating pubertal development in 8,689 healthy girls in the mid-1980s. Rohrer et al [1] observed that T1D girls develop thelarche 6 months later than control girls, although the reported age is within the normal range for both groups. The fact that the T1D and control groups were not recruited simultaneously does not limit the conclusions of this study, since the trend for an earlier onset of puberty in healthy girls would increase the difference between both groups.…”
Section: Pubertal Development and Ovarian Function In Girls With T1dmentioning
confidence: 98%
See 3 more Smart Citations